The Impacts of SLC22A1 rs594709 and SLC47A1 rs2289669 Polymorphisms on Metformin Therapeutic Efficacy in Chinese Type 2 Diabetes Patients - Di Xiao; Yu Guo; Xi Li; Ji-Ye Yin; Wei Zheng; Xin-Wen Qiu; Ling Xiao; Rang-Ru Liu; Sai-Ying Wang; Wei-Jing Gong; Hong-Hao Zhou; Zhao-Qian Liu (International Journal of Endocrinology)
Background. We aimed to investigate the distributive characteristics of SLC22A1 rs594709 and SLC47A1 rs2289669 polymorphisms and their influence on metformin efficacy in Chinese T2DM patients. Methods. The distributions of SLC22A1 rs594709 and SLC47A1 rs2289669 polymorphisms were determined in 267 T2DM patients and 182 healthy subjects. Subsequently, 53 newly diagnosed patients who received metformin monotherapy were recruited to evaluate metformin efficacy. Results. No significant difference was found between T2DM patients and healthy subjects in SLC22A1 rs594709 and SLC47A1 rs2289669 allele frequencies and genotype frequencies. After metformin treatment, SLC22A1 rs594709 GG genotype patients showed a higher increase in FINS (p=0.015) and decrease in HOMA-IS (p=0.001) and QUICKI (p=0.002) than A allele carriers. SLC47A1 rs2289669 GG genotype patients had a higher decrease in TChol (p=0.030) and LDL-C (p=0.049) than A allele carriers. Among SLC22A1 rs594709 AA genotype, patients with SLC47A1 rs2289669 AA genotype showed a higher decrease in FBG (p=0.015), PINS (p=0.041), and HOMA-IR (p=0.014) than G allele carriers. However, among SLC22A1 rs594709 G allele carriers, SLC47A1 rs2289669 AA genotype patients showed a higher decrease in TChol (p=0.013) than G allele carriers. Conclusion. Our data suggest that SLC22A1 rs594709 and SLC47A1 rs2289669 polymorphisms may influence metformin efficacy together in Chinese T2DM patients.